Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1515/znc-2010-1-219
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Localization of Bombyx mori V-ATPase 16 kDa Subunit c

Abstract: V-ATPase plays a central role in lepidopteran midgut ion transport physiology, and lepidopteran midgut turned out to be a model tissue for the study of V-ATPase. In the present study, the 5'-RACE method is used to obtain the 5'-UTR of V-ATPase c subunit gene from Bombyx mori. Sequence analysis of the promoter region and 3'-UTR of V-ATPase c subunit gene revealed that the transcription of the V-ATPase c subunit gene may be regulated by multi-ways. RT-PCR analysis showed that B. mori V-ATPase c subunit mRNA expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…S1). Our observations are consistent with the published literature where similar observations were made in BmN cells from B. mori 26 . Additionally, Nelson reported that V‐ATPase is principally located in vacuolar membranes, including endosomes, lysosomes, and clathrin‐coated vesicles 27 .…”
Section: Disscusionsupporting
confidence: 93%
See 1 more Smart Citation
“…S1). Our observations are consistent with the published literature where similar observations were made in BmN cells from B. mori 26 . Additionally, Nelson reported that V‐ATPase is principally located in vacuolar membranes, including endosomes, lysosomes, and clathrin‐coated vesicles 27 .…”
Section: Disscusionsupporting
confidence: 93%
“…Our observations are consistent with the published literature where similar observations were made in BmN cells from B. mori. 26 Additionally, Nelson reported that V-ATPase is principally located in vacuolar membranes, including endosomes, lysosomes, and clathrin-coated vesicles. 27 The localization of LmV-ATPase-c in endosomes suggests that it likely participates in various basic cellular processes, but further study is clearly needed to verify its exact functions.…”
Section: Disscusionmentioning
confidence: 99%